Diffusivities and atomic mobilities in bcc Ti–Mo–Ta alloys. (March 2022) - Bai, Weimin; Nie, Jingjing; Hu, Songsong; Wang, Xinming; Li, Zhi; Yin, Fucheng; Lin, Jianguo; Zhang, Ligang; Liu, Libin
Abstract: Mo and Ta are two important β stable elements that can enhance the fatigue strength and reduce the elastic modulus of titanium alloy, and can significantly improve the biocompatibility of titanium alloy. It is significant to study the diffusion behavior in β Ti–Mo–Ta alloy for understanding the microstructure evolution in production process and developing new alloys. In this study, using several diffusion couples, the interdiffusion coefficients and impurity diffusion coefficients in β Ti–Mo–Ta alloy were extracted via Whittle-Green method and Hall method. The atomic mobilities in bcc phase in Ti–Mo–Ta system were obtained by assessing the experimental data using CALPHAD (CALculation of PHAse Diagrams) method. Simulations of the diffusion process in the diffusion couples were implemented using DICTRA Module in Thermo-Calc software. The calculated data were in good agreement with the experimental data, confirming the accuracy of the database. Highlights: The diffusion behaviors in bcc Ti–Mo–Ta alloys were studied at 1373 K and 1473 K. The atomic mobilities in bcc Ti–Mo–Ta system were obtained using CALPHAD method. Calculations and simulation were proceeded to examine the accuracy of the parameters.